2015
DOI: 10.3892/etm.2015.2725
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of oxygen fluctuation-induced endoplasmic reticulum stress in human lens epithelial cells

Abstract: Abstract. Cataractogenic stresses are associated with the induction of endoplasmic reticulum (ER) stress. However, little is known about oxygen (O 2 )-induced ER stress in the lens. Cataract research has focused on elevated levels of O 2 in lens epithelial cells (LECs). Excessive levels or a lack of O 2 are known to induce ER stress whereas chronic ER stress activates the unfolded protein response (UPR). The present study investigated the hypothesis that the fluctuation of O 2 levels induces a UPR, and may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…O 2 level with the range of 0.1–1.0% can be defined as severe hypoxia, and the O 2 level in lens can effortlessly fall into the severe hypoxia range even in a normal (13–15%) atmospheric O 2 supply (Shui & Beebe, ), especially for diabetic patients (Holekamp et al ., ). Either 0 or 20% atmospheric O 2 induced significant ROS production and cell death in cultured HLECs, accompanied by increased UPR protein and inhibition of the Nrf2/Keap1‐dependent antioxidant protection in LECs, and the results showed that 1% O 2 was appropriate for culturing LECs (Zheng et al ., ).…”
Section: Nrf2 Suppressors and Cataractsmentioning
confidence: 97%
“…O 2 level with the range of 0.1–1.0% can be defined as severe hypoxia, and the O 2 level in lens can effortlessly fall into the severe hypoxia range even in a normal (13–15%) atmospheric O 2 supply (Shui & Beebe, ), especially for diabetic patients (Holekamp et al ., ). Either 0 or 20% atmospheric O 2 induced significant ROS production and cell death in cultured HLECs, accompanied by increased UPR protein and inhibition of the Nrf2/Keap1‐dependent antioxidant protection in LECs, and the results showed that 1% O 2 was appropriate for culturing LECs (Zheng et al ., ).…”
Section: Nrf2 Suppressors and Cataractsmentioning
confidence: 97%
“…Then, Nrf2 initiates the transcription of ARE controlled anti-oxidative enzymes, such as superoxide dismutase (SOD), catalase, glutathione S-transferase (GSTP) 5 , NAD (P)H: quinone oxidoreductase 1 (NQO1) 6 , heme oxygenase-1 (HO-1) 7 , thioredoxin reductase (TrxR), glutathione reductase (GR) and glutathione-S-transferase (GST) 8 , 9 , which detoxify ROS through glutathione (GSH) regulation 10 . Nrf2 is known as the molecular switch of the Nrf2 signaling (also known as Nrf2/Keap1 or Nrf2/Keap1/ARE signaling) and serves as a foremost component of ROS signaling pathway that can be activated by oxidative stress inducers, such as sulforaphane (SF) 11 , hyperoside 12 , hyperglycemia 3 and inhibited by oxidative stress factors such as homocysteine (Hcy) 13 , O 2 fluctuation 14 and hypoglycemia under hypoxia 15 . The protective role of Nrf2 against oxidative stress in ocular diseases has been explained in the following researches: DR 3 , retinal I/R injury 4 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Lens-specific cataract formation might be induced by a predominant interaction between lens specific protein(s) and the ER stressor(s). It has been demonstrated that human lens epithelial cells exposed to a certain oxygen environment activated a protective UPR while chronic hypoxic conditions induced ROS production and apoptotic UPR resulting in lens epithelial cell death and lens oxidation (Elanchezhian et al, 2012b; Zheng et al, 2015). Thus, cataract is one of the protein misfolding diseases, and misfolded protein conformation in the ER initiates pathogenic processes and results in misfolded crystallin aggregations.…”
Section: Cataractogenic Stress and The Er Stress/uprmentioning
confidence: 99%